2022
DOI: 10.21203/rs.3.rs-1549257/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APN deficiency accelerates brain aging via mitochondrial associated neuroinflammation

Abstract: A wide spectrum of changes occur in the brain with age, from molecular to morphological aspects, and inflammation accompanied by mitochondria dysfunctions is one of the significant processes and factors associated with age. Adiponectin (APN), an adipokine important in glucose and lipid metabolism, is involved in the aging; however, their roles in brain aging have not been explored adequately. Here, we aimed to mechanistically illuminate the causal relation of brain aging with APN deficiency via multiple bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Adiponectin deficiency has been associated with increased susceptibility to metabolic disorders and accelerated aging in in vitro conditions. 54–56 Leptin and adiponectin have opposing effects on subclinical inflammation, where leptin upregulates proinflammatory cytokines, such as TNF-α (tumor necrosis factor-alpha) and IL-6 (interleukin-6), whereas adiponectin downregulates their expression. 57,58 The inverse relationship between leptin and adiponectin has been observed in obesity, diabetes, and CAD studies and has been suggested as a useful index in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin deficiency has been associated with increased susceptibility to metabolic disorders and accelerated aging in in vitro conditions. 54–56 Leptin and adiponectin have opposing effects on subclinical inflammation, where leptin upregulates proinflammatory cytokines, such as TNF-α (tumor necrosis factor-alpha) and IL-6 (interleukin-6), whereas adiponectin downregulates their expression. 57,58 The inverse relationship between leptin and adiponectin has been observed in obesity, diabetes, and CAD studies and has been suggested as a useful index in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are one of the most complex and important organelles present in eukaryotes, which convert organic matter into carbon dioxide and water through redox reactions (9). Mitochondrial dysfunction leads to the irregular transfer of electrons generated by redox reactions to oxygen, water, or their intermediate states, thus forming large quantities of reactive oxygen species (ROS), eventually leading to cell death (10,11). Mitophagy, a special form of autophagy, is a…”
Section: Introductionmentioning
confidence: 99%